Proceedings of the 50th Annual ACM SIGACT Symposium on Theory of Computing 2018
DOI: 10.1145/3188745.3188968
|View full text |Cite
|
Sign up to set email alerts
|

A converse to Banach's fixed point theorem and its CLS-completeness

Abstract: Banach's fixed point theorem for contraction maps has been widely used to analyze the convergence of iterative methods in non-convex problems. It is a common experience, however, that iterative maps fail to be globally contracting under the natural metric in their domain, making the applicability of Banach's theorem limited. We explore how generally we can apply Banach's fixed point theorem to establish the convergence of iterative methods when pairing it with carefully designed metrics.Our first result is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 24 publications
(23 reference statements)
0
31
1
Order By: Relevance
“…Beyond equilibrium computation and its applications to Economics and Game Theory, the study of total search problems has found profound connections to many scientific fields, including continuous optimization [DP11,DTZ18], combinatorial optimization [SY91], query complexity [BCE + 95], topology [GH19], topological combinatorics and social choice theory [FG18,FG19,FRHSZ20b,FRHSZ20a], algebraic combinatorics [BIQ + 17, GKSZ19], and cryptography [Jeř16,BPR15,SZZ18]. For a more extensive overview of total search problems we refer the reader to the recent survey by Daskalakis [Das18].…”
Section: Further Related Workmentioning
confidence: 99%
“…Beyond equilibrium computation and its applications to Economics and Game Theory, the study of total search problems has found profound connections to many scientific fields, including continuous optimization [DP11,DTZ18], combinatorial optimization [SY91], query complexity [BCE + 95], topology [GH19], topological combinatorics and social choice theory [FG18,FG19,FRHSZ20b,FRHSZ20a], algebraic combinatorics [BIQ + 17, GKSZ19], and cryptography [Jeř16,BPR15,SZZ18]. For a more extensive overview of total search problems we refer the reader to the recent survey by Daskalakis [Das18].…”
Section: Further Related Workmentioning
confidence: 99%
“…These are results which show that if an iterative method converges for some set X on a metric space with metric d, then there is a (potentially different) metric d for which the map is a contraction mapping for any Lipschitz constant q. In particular in [9] the following converse theorem is proved Theorem A.1 (Theorem 1 of [9]). Let (X, d) be a complete, proper metric space and F : X −→ X be continuous with respect to d such that F has a unique fixed point x * , and the iteration x i ← F (x i−1 ) converges to x * with respect to d, and there exists an open neighbourhood U of x * such that…”
Section: A Converses To Banach's Fixed Point Theoremmentioning
confidence: 98%
“…The authors of [9] illustate this in terms of the power method for matrices. Indeed in [9][Proposition 1] it is shown that if we restrict to real matrices A (with eigenvalues |λ 1 | > |λ 2 | ≥ . .…”
Section: A Converses To Banach's Fixed Point Theoremmentioning
confidence: 99%
“…Its corresponding computational problem Contraction, is to find a fixed point of a given contraction map. Some versions of Contraction have been shown complete for CLS, a subclass of PPAD [11,12,16]. The search for Brouwer fixpoints (including discretised versions of Brouwer functions) is PPAD-complete for most variants of the problem [28,7], which is why we say the HBT is "Brouwer-like".…”
Section: Other Related Workmentioning
confidence: 99%